2020
DOI: 10.18231/2395-1451.2018.0116
|View full text |Cite
|
Sign up to set email alerts
|

Study of refractive errors in medical students

Abstract: Introduction: Refractive errors are apparently more prevalent among the high educational group and have become a huge economic and social burden. 1 Materials and Methods: The study was conducted at Era's Lucknow Medical College and Hospital and included 420 medical students of consecutive 4ys (2013)(2014)(2015)(2016). Refractive error was assessed under cycloplegia using Snellen's visual acquity drum and streak retinoscope. The students were categorized according to their refractive error and the prevalence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This result is in accordance with studies in the Scandinavian countries, where the prevalence rate of refractive errors among the medical students was 50.3%, [6][7] and in India, where it varied from 54-73%. [8][9][10][11][12][13][14][15][16] However there was a much higher prevalence of 80-90% among medical students in Singapore 4 and Taiwan. 5 Among the students who had refractive errors (51.4%), the leading type was simple myopia seen in 42.9 %, followed by simple astigmatism in 7.1 % and simple hypermetropia in 1.4%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is in accordance with studies in the Scandinavian countries, where the prevalence rate of refractive errors among the medical students was 50.3%, [6][7] and in India, where it varied from 54-73%. [8][9][10][11][12][13][14][15][16] However there was a much higher prevalence of 80-90% among medical students in Singapore 4 and Taiwan. 5 Among the students who had refractive errors (51.4%), the leading type was simple myopia seen in 42.9 %, followed by simple astigmatism in 7.1 % and simple hypermetropia in 1.4%.…”
Section: Discussionmentioning
confidence: 99%
“…12 A similar study in Odisha, India estimated a similar prevalence of refractive error as 56%, with myopia accounting for 54.5% followed by astigmatism 31.3%. 14 A study of refractive errors among medical students in Lucknow, done by Garg et al 16 reported the prevalence of refractive error as 54%, with a higher prevalence of myopia accounting for 77.7%. Studies on medical students in Denmark and Norway yielded a relatively-low prevalence rates of myopia accounting for 50% and 50.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations